Project: ArctiChildren InNet - Kostenius, Catrine; Bergmark, Ulrika; Hertting, Krister; Nyström, Lena; Lögdberg, Ulrika; Lindqvist, Anna-Karin; Grape, Monica (Luleå tekniska universitet, Hälsa och rehabilitering, 2014)
Sedan 2003 har jag varit delaktig i Arctic Children, ett forsknings- och utvecklingsprojekt med övergripande mål att förbättra barn och ungdomars psykosocialahälsa och välbefinnande. Ett givande samarbete som inkluderar norra delarna av Sverige, Finland, Norge och Ryssland som sedan 2012 gått in i projektets tredje fas för att ta sig an gemensamma utmaningarna kopplat till barn och ungdomars psykiska, psykologiska, emotionella, sociala och andliga hälsa med hjälp av empowerment och informations-och kommunikationsteknik (IKT). Publikationer: Creating opportunities for diversity and unpredictability: inviting children to be co-researchers; Fun, feasible and functioning: Students’ experiences of a physical activity intervention; ArctiChildren project: A good example of giving voice and space to students in an international cross-border network; Moving From Idea to Action: Promoting Physical Activity by Empowering Adolescents; eHealth and eLearning Go Hand in Hand; Health promoting interactive technology: Finnish, Norwegian, Russian and Swedish students' reflections; From ArctiChildren to ArctiChildren InNet: Some Reflections; “We Did It Together!”: Teacher’s Experiences of Using Interactive Technology in Classroom; Empowering opportunities when the tablet computer meets the school context?: Teachers’ and school children’s usage and experiences; How can interactive technology be used to facilitate health and well-being in school?: Reflections from school children in the Barents region; Active@school: Promoting Physical Activity with Interactive Technology by Empowering Schoolchildren; Peers, parents and phones: Swedish adolescents and health promotion; With Gratitude to the Schoolchildren; Together for Schoolchildren’s Health!: Arguments for Cross-border Collaboration to Promote Schoolchildren’s Health through ICT Applications in the Barents Region; Experiences of Cross-Border Collaboration to Promote Schoolchildren’s Health; Empowering School eHealth Model in the Barents Region; Aktiviteter: ArctiChildren ...